Role of α2β1 integrins in mediating cell shape on microtextured titanium surfaces. Issue 2 (7th May 2014) - Lai, Min; Hermann, Christopher D.; Cheng, Alice; Olivares‐Navarrete, Rene; Gittens, Rolando A.; Bird, Meredith M.; Walker, Marcus; Cai, Ye; Cai, Kaiyong; Sandhage, Kenneth H.; Schwartz, Zvi; Boyan, Barbara D.
Abstract: Surface microroughness plays an important role in determining osteoblast behavior on titanium. Previous studies have shown that osteoblast differentiation on microtextured titanium substrates is dependent on alpha‐2 beta‐1 (α2β1) integrin signaling. This study used focused ion beam milling and scanning electron microscopy, combined with three‐dimensional image reconstruction, to investigate early interactions of individual cells with their substrate and the role of integrin α2β1 in determining cell shape. MG63 osteoblast‐like cells on sand blasted/acid etched (SLA) Ti surfaces after 3 days of culturing indicated decreased cell number, increased cell differentiation, and increased expression of mRNA levels for α1, α2, αV, and β1 integrin subunits compared to cells on smooth Ti (PT) surfaces. α2 or β1 silenced cells exhibited increased cell number and decreased differentiation on SLA compared to wild‐type cells. Wild‐type cells on SLA possessed an elongated morphology with reduced cell area, increased cell thickness, and more apparent contact points. Cells on PT exhibited greater spreading and were relatively flat. Silenced cells possessed a morphology and phenotype similar to wild‐type cells grown on PT. These observations indicate that surface microroughness affects cell response via α2β1 integrin signaling, resulting in a cell shape that promotes osteoblastic differentiation. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 564–573, 2015.